Pre-habilitation Before Vestibular Schwannoma Surgery—Impact of Intratympanal Gentamicin Application on the Vestibulo-Ocular Reflex - Tarnutzer, Alexander A.; Bockisch, Christopher J.; Buffone, Elena; Huber, Alexander M.; Wettstein, Vincent G.; Weber, Konrad P. (Frontiers in Neurology, 2021)
Background: Patients with vestibular schwannoma that show residual peripheral-vestibular function before surgery may experience sudden and substantial vestibular loss-of-function after surgical resection. To alleviate the sudden-loss of peripheral-vestibular function after vestibular-schwannoma (VS)-resection, presurgical intratympanic gentamicin application was proposed. Objective: We hypothesized that this approach allows for a controlled reduction of peripheral-vestibular function before surgery, but that resulting peripheral-vestibular deficits may be canal-specific with anterior-canal sparing as observed previously in systemic gentamicin application. Methods: Thirty-four patients (age-range=27-70y) with unilateral VS (size=2-50mm) were included in this retrospective single-center trial. The angular vestibulo-ocular reflex (aVOR) was quantified before and after (29.7±18.7d, mean±1SD) a single or two sequential intratympanic gentamicin applications by use of video-head-impulse testing. Both aVOR-gains, cumulative saccadic amplitudes and overall aVOR-function were retrieved. Statistical analysis was done using a generalized linear model. Results: At baseline, loss-of-function of the horizontal (20/34) and posterior (21/34) canal was significantly (p<0.001) more frequent than of the anterior canal (5/34). After gentamicin application, loss-of-function of the horizontal (32/34) or posterior (31/34) canal remained significantly (p≤0.003) more frequent than of the anterior canal (18/34). For all ipsilesional canals significant aVOR-gain reductions and cumulative-saccadic-amplitude increases were noted after gentamicin. For the horizontal canal loss-of-function was significantly larger (increase in cumulative-saccadic-amplitude: 1.6±2.0 vs. 0.8±1.2, p=0.007) or showed a trend to larger changes (decrease in aVOR-gain: 0.24±0.22 vs. 0.13±0.29, p=0.069) than for the anterior canal. Conclusions: Intratympanic gentamicin application resulted in a substantial reduction in peripheral-vestibular function in all three ipsilesional canals. Relative sparing of anterior-canal function noted at baseline was preserved after gentamicin treatment. Thus, presurgical intratympanic gentamicin is a suitable preparatory procedure for reducing the drop in peripheral-vestibular function after VS-resection. The reasons for relative sparing of the anterior canal remain unclear.